Power outage detection methods for theoperation of a shunt active power flter as energy backup system - Exposto, Bruno (2014)
This paper presents the study of power outage detection methods that can be applied to a Shunt Active Power Filter (SAPF) with energy backup capability. SAPFs can successfully compensate Power Quality problems related with distorted or unbalanced currents and low power factor. Future Smart Grids will combine devices, control strategies and functionalities to increase the grid reliability and the power management capability. One of the main tools necessary to enable these features is the information of what is occurring in all the smart grid parts. In this context the fast detection of power outages is critical, so this paper also contributes for the discussion of the best ways to extract information in the context of future smart grids. The combination of information and flexible devices in a smart grid will enable the implementation of collective awareness systems, which can deal with different electrical grid problems and situations in an organic manner.